Constructing Brand Identity through Language: A Critical Discourse Analysis of Indonesian Indie Publishers’ Digital Branding: Konstruksi Identitas Merek melalui Bahasa: Analisis Wacana Kritis terhadap Digital Branding Penerbit Indie Indonesia - Nasrawati; Seli Marlina Radja Leba; Rawuh Yuda Yuwana; Marantika Lia Kristyasari (Jurnal Bastra (Bahasa dan Sastra), 2026)
Digital communication has transformed branding into a discursive practice in which language constructs organizational identity and fosters audience engagement. This study investigates the linguistic strategies used by Indonesian indie publishers in digital branding by integrating Critical Discourse Analysis, Systemic Functional Linguistics, and Appraisal Theory. Using a qualitative multiple-case study design, the research analyzed digital texts from Instagram, Facebook, TikTok, and official websites of selected indie publishers. Data were examined through lexical, interpersonal, evaluative, and discursive analyses to identify recurring branding patterns. The findings show four dominant strategies: literacy-oriented lexical choices, inclusive interpersonal language, positive appraisal resources, and narrative framing. Indonesian indie publishers do not rely mainly on overt commercial promotion, but position themselves as collaborative literacy partners committed to education, knowledge dissemination, and community empowerment. The study implies that strategic language use can build persuasive, credible, and community-oriented digital branding in the publishing sector across adaptive digital communication platforms effectively.